From livestock herding to cooperative farming in the Somali communities of Dolo Ado and Bokolmayo districts of Ethiopia - Dessalegn, Mengistu; Mekuria, Wolde; Singh, Radhika; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
This study was conducted in the traditional pastoralist communities of Dolo Ado and Bokolmayo districts in the Somali Region of Ethiopia. These are refugee-hosting communities where the World Food Programme (WFP) is providing humanitarian and livelihood support. This research was designed in partnership with WFP with the expectation that its findings may provide lessons that can inform the organization’s program activities benefiting refugee-hosting communities and integrated refugees.